The Mediating Role of Endocrine Factors in the Positive Relationship Between Fat Mass and Bone Mineral Content in Children Aged 9–11 Years: The Physical Activity and Nutrition in Children Study - Constable, Annie M.; Vlachopoulos, Dimitris; Barker, Alan R.; Moore, Sarah A.; Soininen, Sonja; Haapala, Eero A.; Väistö, Juuso; Jääskeläinen, Jarmo; Voutilainen, Raimo; Auriola, Seppo; Häkkinen, Merja R.; Laitinen, Tomi; et al. (Frontiers in Endocrinology, 2022)
Introduction: We aimed to investigate whether the relationship between fat mass and bone mineral content (BMC) is mediated by insulin, leptin, adiponectin, dehydroepiandrosterone sulphate, testosterone and estradiol in children aged 9-11 years. Materials and Methods: We utilised cross-sectional data from the Physical Activity and Nutrition in Children study (n = 230 to 396; 112 to 203 girls). Fat mass and BMC were assessed with dual-energy X-ray absorptiometry. Endocrine factors were assessed from fasted blood samples. We applied the novel 4-way decomposition method to analyse associations between fat mass, endocrine factors, and BMC. Results: Fat mass was positively associated with BMC in girls (ß = 0.007 to 0.015, 95% confidence interval (CI) 0.005 to 0.020) and boys (ß = 0.009 to 0.015, 95% CI 0.005 to 0.019). The relationship between fat mass and BMC was mediated by free leptin index in girls (ß = -0.025, 95% CI -0.039 to -0.010) and boys (ß = -0.014, 95% CI -0.027 to -0.001). The relationship between fat mass and BMC was partially explained by mediated interaction between fat mass and free leptin index in boys (ß = -0.009, 95% CI -0.013 to -0.004) and by interaction between fat mass and adiponectin in girls (ß = -0.003, 95% CI -0.006 to -0.000). Conclusion: At greater levels of adiponectin and free leptin index, the fat mass and BMC relationship becomes less positive in girls and boys respectively. The positive association between fat mass with BMC was largely not explained by the endocrine factors we assessed. Trial registration number: NCT01803776 Date of registration: 4/03/2013